2011
DOI: 10.1007/978-3-642-22878-0_31
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguities in the Early Stages of Public Sector Enterprise Architecture Implementation: Outlining Complexities of Interoperability

Abstract: Abstract. In recent years the development of eGovernment has increasingly gone from service provision to striving for an interoperable public sector, with Enterprise Architectures being an increasingly popular approach. However, a central issue is the coordination of work, due to differing perceptions among involved actors. This paper provides a deepened understanding of this by addressing the question of how differing interpretations of interoperability benefits affect the coordination in the early stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Recent research such as (Dutta et al 2017;Sedek et al 2013;Cellary and Strykowski 2009) found that SOA-based architecture is more suitable for Digital Government and according to our findings, most architecture (57%) adopts SOA. Other literature (Agarwal et al 2017;Janssen and Kuk 2006;Zheng and Zheng 2011;Larsson 2011) revealed that Enterprise Architecture has become increasingly popular. Considering the technological aspects of the reviewed architectures, we found that the majority of the architecture employs XML-based technologies, i.e., WSDL, RDF SPARQL, and Web Services, i.e., SOAP and REST, which shows that XML-based technologies and Web Services are the most natural choice candidate technologies and standards to support and base Digital Government systems Meneklis et al (2005).…”
Section: Existing Architecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research such as (Dutta et al 2017;Sedek et al 2013;Cellary and Strykowski 2009) found that SOA-based architecture is more suitable for Digital Government and according to our findings, most architecture (57%) adopts SOA. Other literature (Agarwal et al 2017;Janssen and Kuk 2006;Zheng and Zheng 2011;Larsson 2011) revealed that Enterprise Architecture has become increasingly popular. Considering the technological aspects of the reviewed architectures, we found that the majority of the architecture employs XML-based technologies, i.e., WSDL, RDF SPARQL, and Web Services, i.e., SOAP and REST, which shows that XML-based technologies and Web Services are the most natural choice candidate technologies and standards to support and base Digital Government systems Meneklis et al (2005).…”
Section: Existing Architecturesmentioning
confidence: 99%
“…However, government structure is much broader than a single organization, and it is comprised of separate agencies (ministries, governorates, and municipalities) (Janssen et al 2013;Klischewski and Abubakr 2010). Considering the structure of government, various other challenges of EA are widely known in Digital Government, such as implementation ability and governance (Isomäki and Liimatainen 2008;Klischewski and Abubakr 2010), legislative and socially rooted boundaries (Klischewski and Abubakr 2010;Larsson 2011;Isomäki and Liimatainen 2008), and lack of shared infrastructure (Klischewski and Abubakr 2010;Isomäki and Liimatainen 2008). Furthermore, Larsson Larsson (2011) argues that EA in the public sector, to a large extent, is immature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Para el sector público y los gobiernos locales, la AE puede brindar la vista integral de gestión requerida por éstos, ya que soporta una visión sociotécnica de las organizaciones gubernamentales locales, incluidas las personas, la información, y la tecnología (Saha, 2009;Larsson, 2011). Desde una visión holística de la organización, la AE está representada desde cuatro perspectivas (Saha, 2007; Jin & Kung, 2010): arquitectura de negocios, arquitectura de aplicaciones, arquitectura de tecnología y arquitectura de datos.…”
Section: Arquitectura Empresarialunclassified
“…Enterprise Architecture (EA) has been seen as a promising tool for improving information systems interoperability, standardization and business-IT alignment in the rapidly changing world of public administration [5], [23]. However, experiences in using EA in the public sector are mixed [10], [13], [18].…”
Section: Introductionmentioning
confidence: 99%